Perceptions of the Colombian business sector regarding its role in the post-conflict (2019)
The objective of this research is to analyze the role of the Colombian business sector in the post-conflict scenario and the construction of peace from the perception of entrepreneurs. It is a study framed in the empirical-analytical paradigm and the quantitative approach. The research has an explanatory level and non-experimental design. A questionnaire was used as a tool that was applied to 200 companies, from the main cities of Colombia, belonging to the commercial, services, manufacturing and financial sectors. The main findings show that entrepreneurs are willing to participate in post-conflict from different mechanisms, although there is a lack of knowledge of most of these. Likewise, employers’ concerns about the scope of their participation in the post-conflict are evident, which allows concluding the need for the State to establish clearly and precisely the linkage of the private sector in the process, and the ways of articulating the institutional activity with the possible support of companies.